Epigenetic Influences in the Aetiology of Cancers Arising from Breast and Prostate: A Hypothesised Transgenerational Evolution in Chromatin Accessibility. (3rd February 2013) - Martin, Francis L.
Abstract : Epidemiological studies have consistently supported the notion that environmental and/or dietary factors play a central role in the aetiology of cancers of the breast and prostate. However, for more than five decades investigators have failed to identify a single cause-and-effect factor, which could be implicated; identification of a causative entity would allow the implementation of an intervention strategy in at-risk populations. This suggests a more complex pathoaetiology for these cancer sites, compared to others. When one examines the increases or decreases in incidence of specific cancers amongst migrant populations, it is notable that disease arising in colon or stomach requires one or at most two generations to exhibit a change in incidence to match that of high-incidence regions, whereas for breast or prostate cancer, at least three generations are required. This generational threshold could suggest a requirement for nonmutation-driven epigenetic alterations in the F0/F1 generations (parental/offspring adopting a more westernized lifestyle), which then predisposes the inherited genome of subsequent generations to mutagenic/genotoxic alterations leading to the development of sporadic cancer in these target sites. As such, individual susceptibility to carcinogen insult would not be based per se on polymorphisms in activating/detoxifying/repair enzymes, but on elevated accessibility of crucial target genes (e.g., oncogenes, tumour suppressor genes) or hotspots therein to mutation events. This could be termed a genomic susceptibility organizational structure (SOS). Several exposures including alcohol and heavy metals are epigens (i.e., modifiers of the epigenome), whereas others are mutagenic/genotoxic, for example, heterocyclic aromatic amines; humans are continuously and variously exposed to mixtures of these agents. Within such a transgenerational multistage model of cancer development, determining the interaction between epigenetic modification to generate a genomic SOS and genotoxic insult will facilitate a new level of understanding in the aetiology of cancer.